Quantifying hemodynamics within an aneurysm exposed to prolonged exercise levels. (February 2020) - Varshney, Mehul; Haani Farooqi, M.; Usmani, Abdullah Y.
Highlights: The present study explores the possibility of non-invasive treatment of Abdominal Aortic Aneurysm (AAA), while exposing the patients to varying exercise levels (mild and moderate) of the heart. The primary goal is to select an optimum level of exercise, to be advised by clinicians for disease treatment. This is achieved through comparing the flow dynamics obtained under mild and moderate activity against that of resting conditions. Numerical simulations within a AAA are performed (using ANSYS Fluent) to exploit the spatio-temporal evolution of flow patterns and vorticity. The Reynolds number considered are repeak  = 200, 750 and 1200 whereas Womersley number ( α ) varies as 11.59, 14.72 and 17.84 Hz, under resting, mild and moderate exercise, respectively. Hemodynamic indicators are quantified in terms of time-averaged wall shear stress (TAWSS), oscillatory shear index (OSI). The trajectories of vortex core movement (using Q - criterion) are correlated to pressure peaks attained at the wall. The chances of disease progression (subjected to a particular exercise) are further quantified through evaluating the particle residence index (PRI). This is obtained through employing the Discrete Phase Material (DPM) technique (available in ANSYS Fluent), while releasing massless tracer particles within the aneurysmal domain. The overall analysis in the biomedical context is used to select an optimum exercise level for disease treatment. Abstract: Background and objective: Non-invasive treatment of unruptured Abdominal Aortic Aneurysm involves subjecting the patients to certain physiological levels of the heart. Flow topology ( Repeak  = 200–1200, frequency: f  = 1.18–2.41 Hz) within an aneurysm geometry (2-D) under resting and exercise (mild and moderate) conditions are explored in the present study. Blood is assumed to be Newtonian in nature. Spatio-temporal evolution of the flow patterns and vorticity are established. Hemodynamic indicators (TAWSS and OSI), movement of vortex cores and Particle Residence Index (PRI) are quantified to select an optimum exercise level in attenuating the disease. Methods: The finite volume method is employed for numerical solutions using ANSYS-Fluent Ⓡ software. The SIMPLE scheme has been used for the pressure-velocity coupling. Least Square cell-based method is used for the spatial discretization of the gradients. Second order upwind scheme is considered for discretization of the pressure term. Third order upwind (QUICK) scheme is used to discretize the momentum equation. First order Implicit Scheme was used for the discretization of the temporal terms. Discrete Phase Material (DPM) technique is employed throughout, to visualize the signature of particle deposits within the aneurysm. Results: Vortex impingement induces a pressure peak within the aneurysm (moderate) while the peaks are anchored at the proximal and distal ends under resting and mild conditions. Along the averaged flow separation zone, exercise increases the maximum TAWSS from 1.21 N/m 2 (mild) to 9.3 N/m 2 (moderate). The distal site is exposed to oscillatory loading (OSI = 0.5) under mild activity whereas the loading becomes distributed almost over the entire wall, when subjected to moderate conditions. This in turn, reduces the time involved in 50 percent clearance of particles (PRI = 0.5) from 10.56 s (resting) to 3.98 s (mild) and 0.87 s (moderate), respectively. Conclusions: Resting conditions manifests the aneurysmal wall to recirculating fluid for most of cycle time. Moderate exercise exhibits the least particle clearance time, but it exposes the aneurysmal wall and the distal end to high pressure, which otherwise has low intensity under mild activity. This in turn establishes that mild exercise for prolonged duration can be an optimum level for non-invasive aneurysmal treatment.